An assessment of distributed state estimation. (1st January 2013) - Mahmoud, Magdi S.; Sabih, Muhammad
State estimation is an important topic in the study of dynamical systems. The problem of estimation can be structured into three categories: 1) centralised scheme; 2) decentralised scheme; 3) distributed scheme. Distributed estimation is a compromise between completely centralised and decentralised versions of estimation. In this paper, we will provide an assessment of distributed estimation based on Kalman filtering techniques for large-scale or sensor networks. In simulation, a second order dynamical system is employed in a scenario of ten sensor nodes. The sensor nodes attempt to estimate the states of the dynamical system with embedded consensus filters. The results show that the distributed estimation algorithm effectively approximates the central Kalman filter. It is concluded that the distributed estimation techniques for distributed dynamical system requires further extensive research.